2020
DOI: 10.1177/2158244020922980
|View full text |Cite
|
Sign up to set email alerts
|

Self-Caging or Playing With the Edge? News Selection Autonomy in Authoritarian China

Abstract: This article studies how the political affiliation and administrative rank of news organizations in a nondemocratic setting affect news selection autonomy. While existing studies have found that further commercialization contributes to more news selection autonomy, the extent to which political affiliation and administrative rank of news media explain autonomy remains unknown. Eight Chinese news organizations of varying political affiliations and administrative ranks were thus selected to compare their news an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Previous studies have attempted to make connections between the rank of a newspaper in China and its autonomy and have found that the higher the ranking of the paper, the lower its autonomy. For non-party newspapers, however, a higher rank is usually associated with a higher level of autonomy (Kuang, 2012).…”
Section: The Role Of Official Regulations and International Media Plamentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have attempted to make connections between the rank of a newspaper in China and its autonomy and have found that the higher the ranking of the paper, the lower its autonomy. For non-party newspapers, however, a higher rank is usually associated with a higher level of autonomy (Kuang, 2012).…”
Section: The Role Of Official Regulations and International Media Plamentioning
confidence: 99%
“…In a controlled society such as China, ranking is important with regard to surviving against local competition, but its importance becomes secondary when party or government interests appear. For the Chinese media, a ranking is less important than the media-government or 'independent' orientation (Kuang, 2012). In some ways, it indicates that there is less government control over the content.…”
Section: The Role Of Official Regulations and International Media Plamentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a growing recognition that some independent reporting can actually help authoritarian regimes in developing countries (See Bennett & Livingston, 2018;J. Chen & Xu, 2017;Kuang, 2020;Kuang & Wang, 2020;Kuang & Wei, 2017;Santo & Costa, 2016;Sunstein, 2018). Some scholars in particular have argued that some central government has benefited from an active captured media that helps keep local officials in check, although it is largely blocked from serious reporting on malfeasance at higher levels of government (Liebman, 2011;Shirk, 2011;Zhao, 2000).…”
Section: Introductionmentioning
confidence: 99%